2020
DOI: 10.1111/dth.14255
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐poor plasma gel vs platelet‐rich plasma for infraorbital rejuvenation: A clinical and dermoscopic comparative study

Abstract: Infraorbital dark circles and tear trough deformity are considered common aesthetic problems. Numerous therapeutic modalities have been suggested with variable outcomes. The aim of this study was to compare the efficacy of platelet-poor plasma (PPP) gel vs platelet-rich plasma (PRP) in infraorbital rejuvenation. A total of 68 females presented with dark circles and/or tear trough deformity were recruited and treated by PPP gel injection in the right infraorbital region (Group A) and PRP injection in the left i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…Previous studies have demonstrated positive effects of PRP, supporting its clinical use. In contrast, platelet-poor plasma (PPP) has a lower concentration of platelets than PRP [19,20]. Zhang et al [21] confirmed that PPP maintained the phenotype of osteoblastic cells and enhanced the rate of MSC proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated positive effects of PRP, supporting its clinical use. In contrast, platelet-poor plasma (PPP) has a lower concentration of platelets than PRP [19,20]. Zhang et al [21] confirmed that PPP maintained the phenotype of osteoblastic cells and enhanced the rate of MSC proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the direct volumetric filling effect of plasma gel increased skin tone and volume with more glowing appearance. 4,15 Furthermore, the increased time interval between the sessions in the present work, up to 6 weeks, allowed PIH to be greatly reduced, thus giving better outcome at the end of the treatment sessions.…”
Section: Discussionmentioning
confidence: 79%
“…They explained their results by increased fibrinogen concentration in plasma gel more than PRP, in addition to the more likely arrangement of fibrin fibers in bundles creating insoluble net functioning as a scaffold trapping platelets in the injection site. This confirms continued release of their growth factors to enhance tissue restoration and collagen remodeling 4,15. Consequently, F I G U R E 3 A 47-year-old female patient, Fitzpatrick's type III, presented with; (A) striae albae on abdomen since 15 years, (B) Grade 3 improvement (50%-74%…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…There are three kinds of filling materials commonly used in the clinic: autologous filling materials, biological agents, and artificial filling materials. Although the autologous filling materials and biological agents, such as stromal vascular fraction gel (SVF‐gel), microfat graft, platelet‐rich plasma, and acellular dermal matrix, have proven to be effective in tear trough deformity treatment and have no immunogenicity and allergenicity, 11‐14 they also have many limitations and defects. First, the preparation of these self‐materials and biological agents not only has strict requirements for equipment and participant, but also often faces ethical disputes.…”
Section: Discussionmentioning
confidence: 99%